Hydrolytic kinetic resolution as an emerging tool in the synthesis of bioactive molecules - Kumar, Pradeep; Gupta, Priti (Synlett, 2009)
A variety of racemic epoxides mainly derived from terminal olefins, such as aliphatic epoxides, multifuncitonalized epoxides and amine-substituted epoxides, have been successfully resolved into the enantiomerically pure epoxides and diols using Jacobsen's hydrolytic kinetic resolution (HKR) method. The chiral epoxides thus prepared were further elaborated by synthetic manipulation to provide a variety Of Compounds of biological interest. A general synthetic strategy for the construction Of S synlanti-1,3-polyol systems using iterative HKR has been developed, which was subsequently utilized in the synthesis of natural products with a broad range of biological activity. The protocol for the 1,3-polyols was also further extended to the synthesis of 1,3-amino alcohols.
Keywords: Biological activity; Hydrolytic kinetic resolution; Natural products; synthesis; terminal epoxides